Influential Factors Contributing to Stunting in Toddlers - Hermita Bus Umar; Dina Ayuning Tyas; Sirajul Muna; Yayuk Sri Rahayu; Erma Herdyana (CV. Get Press Indonesia, 2025)
This study aimed to investigate the relationship between family socio-economic factors, environmental sanitation, and household physical conditions with the occurrence of stunting among toddlers in densely populated areas of Padang City, West Sumatra. In 2025, a cross-sectional study employing quantitative methods was conducted. The study population included all children aged 24 to 59 months. Using purposive sampling, 75 toddlers were selected based on the following inclusion criteria: measurable anthropometry, possession of a complete KIA/KMS record, and absence of chronic illnesses. Height measurements of toddlers followed the WHO 2006 anthropometric standards, household environmental conditions were assessed through observation, and data were collected via structured interviews. Bivariate analysis indicated a significant association between stunting and specific social and environmental factors. Toddlers from low-income families, with mothers of lower educational attainment, and living in substandard physical environments were found to be more susceptible to growth and development disorders compared to their better-off peers. Both univariate and multivariate analyses demonstrated that stunting is a multifaceted issue influenced by the interplay of the child’s biological age, maternal education level, household physical environment, and family socio-economic status. These findings highlight the necessity of ongoing health education programs to enhance family awareness and capabilities in fulfilling children’s nutritional needs, particularly in environments that are at higher risk for stunting, such as the home setting.